A Systematic Review of Psychological Biases in Gen Z Stock Investment Decisions - Haqibul Mujib; Muhammad Said (Universitas KH. Abdul Chalim Mojokerto, 2024)
Investors tend to make irrational decisions due to psychological considerations. This study aims to analyze the psychological bias among Generation Z toward Islamic stock investment. A review of 73 studies published between 2017 and 2023 was conducted using the Publish or Perish tool. The results show that, in general, the most studied biases are overconfidence bias (84% significance), herding bias (65% significance), and representativeness bias (56% significance). Furthermore, the age of the respondents shows that the most frequently studied biases among young investors are overconfidence bias (83% significance), followed by regret aversion bias (60% significance), and lastly is herding bias (50% significance). Meanwhile, the most studied biases among student investors are representativeness bias (80% significance), overconfidence bias (75% significance), and herding bias (63% significance). The findings of this study are expected to contribute to further research on stock investment decision biases.